A rare case of fatal cerebral phaeohyphomycosis caused by Cladophialophora bantiana in an immunocompetent individual in India - Ranjana Rohilla; Suneeta Meena; Nishant Goyal; Neelam Kaistha (Mazandaran University of Medical Sciences, 2020)
Background and Purpose: Herein, we describe a rare case of fatal cerebral phaeohyphomycosis by Cladophialophora bantiana in an immunocompetent individual without any underlying risk factors. Case report: A 55-year-old female presented with a short history of fever for 1 month, as well as headache, sudden onset of right-sided upper and lower limb weakness, and loss of speech for 10 days. Contrast-enhanced magnetic resonance imaging scan revealed large, peripherally enhancing, well-defined, cystic, space-occupying, axial lesion in the left parietal lobe with a mass effect. The patient was subjected to craniotomy, and the drained pus revealed pigmented septate hyphae in potassium hydroxide mount examination, which was identified as Cladophialophora bantiana. The patient was started on amphotericin B and voriconazole. However, she developed acute respiratory infection leading to multi-organ failure and death on day 27 post-operation. Conclusion: In the absence of comparative trials owing to the rarity of the disease, the radical resection of lesion, drainage of pus, and prolonged targeted antifungal therapy with close postoperative radiological surveillance are the therapeutic measures of choice for patients with brain abscess caused by phaeoid fungi.